An RFQ cooler and buncher for the TRIGA-SPEC experiment - Beyer, Thomas; Blaum, Klaus; Block, M.; Düllmann, Ch. E.; Eberhardt, K.; Eibach, Martin Andreas; Frömmgen, N.; Geppert, C.; Gorges, C.; Grund, J.; Hammen, M.; Kaufmann, S.; et al. (Applied physics. B, Lasers and optics, 2014)
A linear Paul trap for cooling of ion beams, the former cooler for emittance elimination radiofrequency quadrupole (RFQ) at MISTRAL/ISOLDE, has been installed and commissioned at the TRIGA-SPEC experiment located at the research reactor TRIGA Mainz. It is connected to a hot-surface-ionization ion source and a subsequent mass separator for ionization and pre-separation of neutron-rich fission products as delivered from the reactor. The capability of accumulating and bunching ion beams has been implemented to provide low-emittance ion pulses of 250 ns width containing up to 106 ions. A technical description of the upgraded RFQ as well as its characterization with stable ions is presented. Its installation allows delivery of low-emittance ion bunches to the two branches of the TRIGA-SPEC experiment, namely TRIGA-TRAP and TRIGA-LASER.